Evaluation of Her-2/NEU Expression in Cell Block Preparation in Breast Carcinoma In Bangladeshi Woman - Islam, Md Saiful; Nasreen, Mehnaz; Nasreen, Sayeeda; Ahamad, M Shahab Uddin; Bhattacharjee, Pradip; Rahman, Md Zillur (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: HER-2 overexpression is associated with clinical outcomes in patient with breast carcinoma. Particularly this is important for target therapies with the monoclonal antibody (Trastuzumab). With aspirated materials from breast carcinoma more information may be retrieved by making cell blocks like immunohistochemistry in the inoperable breast cancer patient. Materials and methods: This study was carried out on 102 female patients with palpable breast lump, among them 33 malignant cases were found and cell blocks were made from the aspirated materials. HER- 2 statuses were estimated in both the cell block preparation and histopathological blocks separately. Results: Among the 33 cases of duct cell carcinoma, cell blocks of 32 cases were found to be adequate but one of them died before the surgery. HER-2 expression score of 0, 1+, 2+ and 3+ were foundin 14, 7, 5 and 5 cases respectively. All the 14 cell block scored as ‘0’ also showed similar ‘0’ score in their corresponding histologic block. Among the seven cell blocks scored as ‘1+’, 5 cases showed ‘1+’ staining and 2 case showed ‘2+’ staining in their corresponding histologic blocks. Of the ‘2+’ cases in cell block, 2 cases failed to correspond as they scored ‘1+’. Finally 5 cell blocks with ‘3+’ scorecorresponded with that of the histologic blocks.In cell block immunohistochemistry, the sensitivity was 71.43%, specificity 91.67%,positive predictive value of 71.43% and a negative predictive value of 91.67% with an accuracy rate of 87.71% with a highly significant p value (<.001). Cohen’s Kappa test of agreement was 0.814 which means there was a good agreement and Spearman’s rank-correlation analysis found to 0.984 with a p value of < .001 which was highly significant. Conclusion: This study found overexpression of HER-2 can be determined with confidence in the cell block preparation, particularly in the negative cases. JCMCTA 2017 ; 28 (2) : 88-93